COMPLAINT LEVEL COMPARISON OF MUSCULOSKELETAL DISORDER (MSDs) WHEN IRONING WHILE STANDING AND SITTING ON LAUNDRY WORKER ON PEDALANGAN ADMINISTRATIVE VILLAGE SEMARANG - Wini Iriani Putri; Ekawati Ekawati; Suroto Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Laundry is an informal sector business that is not tied to specific hours of work, education, and salary. The characteristics of this work are monotonous and repetitive. In the process of work often occur positions work that is not natural. This unnatural work position is included in the causal factor of musculoskeletal disorder (MSDs). Musculoskeletal complaints are a complaint on the parts of the skeletal muscle felt by a person from a very mild complaint to a very sick complaint. The purpose of this study was to analyze the comparison of the severity of musculoskeletal disorder (MSDs) while ironing and sitting on a laundry worker in the Pedalangan subdistrict of Semarang. The population of this research is all female laundry workers in Pedalangan Village Semarang with 37 people. Based on the research that has been done, obtained as many as 9 of 37 workers (24.3%) have MSDs complaints. The result of analysis of correlation between ironing position and level of complaint found that 77,8% with standing ironing possi have no complaint to MSDs and 22,2% have a little complaint of illness. While for workers with ironing position as much as 73,7% do not have complaints MSDs, 21,1% have few complaints of pain and 0,5% experiencing pain complaints.